Interessenvertretung in globalen Wertschop̈fungsnetzwerken - Theoretische Perspektiven und empirische Befunde; Interest representation in global production networks - Theoretical perspectives and empirical insights - Nora Lohmeyer; Jor̈g Sydow (Industrielle Beziehungen, 2021)
Globale Wertschop̈fungsnetzwerke haben als Organisationsform ok̈onomischer Aktivitaẗen in den letzten Jahrzehnten deutlich an Bedeutung gewonnen. Zuruc̈kgeblieben ist demgegenub̈er trotz der massiven Betroffenheit vieler Interessengruppen - nicht nur, aber besonders der Beschaf̈tigten - eine effektive Vertretung der Interessen. Dies gilt zwar auch fur̈ die zumeist im globalen Norden angesiedelten Leitunternehmen solcher Netzwerke, mehr aber noch fur̈ die an den Netzwerkran̈dern im globalen Sud̈en zu verortenden Organisationen. Gleichwohl finden sich hier wie dort Ansatzpunkte fur̈ eine effektive Vertretung nicht nur, aber vor allem der Interessen von Beschaf̈tigten. – – Global production or value networks have gained significantly in importance as organizational forms of economic activity over the past decades. A by-product of this development, however, despite the widespread concern it has caused among many interest groups - not only, but especially among employees -, is an effective interest representation. This applies to the leading firms of such networks, most of which are located in the global North, but even more so to the organizations located at the networks' peripheries in the global South. Nonetheless, starting points for effective representation of the interests of employees and others are emerging here and there.
Keywords: J50; J80; L14; 330; Gewerkschaft; Globalisierung; Interessenvertretung; Management; Mitbestimmung; Netzwerk; Nicht-Regierungsorganisation; Partizipation; Produktion; Wertschop̈fung; Globalization; interest representation; co-determination; co-management; management; network; non-governmental organization; participation; production; trade union; value creation